THE EFFECTIVENESS OF ENHANCED RECOVERY AFTER SURGERY (ERAS) PROTOCOLS IN BREAST CANCER SURGERY AT A TERTIARY CARE HOSPITAL IN KHYBER PAKHTUNKHWA PAKISTAN - Wahid, Anum; Ali, Irum Sabir; Umar, Usama; Khan, Mah Muneer (Journal of Ayub Medical College Abbottabad, 2024)
Background: Breast cancer treatment outcomes have markedly improved over the years with advancements in knowledge and treatment options. Enhanced recovery after surgery (ERAS) has been introduced recently to enhance post-operative patient wellbeing, attain enhanced recovery for patients who undergo major surgery, and therefore facilitate a drop in hospital length of stay (LOS). These may also furnish an additional advantage of decreasing health care costs while refining the standard of care and patient contentedness. Methods: A quasi-experimental study was conducted in the breast unit of Khyber Teaching Hospital, with a sample size of 30 in each group with a 95% confidence interval and a 5% margin of error. A consecutive non-probability sampling technique was used and the study was conducted in 6 months after taking ethical approval from the ethical review committee MTI, KTH. Comparison was done between both groups for effectiveness, noted with regard to hospital stay, post-op pain and complication rate. Results: The mean age of the patients in the ERAS group was 56.30±5.615 years while the mean age in the non-ERAS group was 56.07±6.11 years. The wound infection was observed in 11 patients with ERAS (36.7%) as compared to 12 (40.0%) without ERAS. Hospital stay was longer in non-ERAS as compared to ERAS with a mean difference of 1.833 and p-value of 0.000 while the post-op VAS mean difference was 1.267 with p value of 0.001. Conclusion: Evidence supports the effectiveness, affordability, and safety of ERAS protocols as it leads to a noticeable decrease in hospitalization duration, resulting in reduced resource consumption and financial burdens. Nonetheless, achieving the mentioned benefits may necessitate strict adherence to the protocol, which could be challenging due to professional, institutional, and personal resistance.